Interpretation of signs and markers in Whiteboard Journal writing in forming political communication for the 2024 Presidential Election - Fadillah, Dani; Gita Pertiwi, Indah (COMMICAST, 2024)
This research aims to examine how political communication messages are conveyed to the public through social media portals. Utilizing a qualitative approach with content analysis as the method, this study investigates posts from the Instagram account @whiteboardjournal. The analysis process is carried out objectively and systematically using semiotic theory, especially Ferdinand de Saussure's concepts of "sign" and "signifier." Data from @whiteboardjournal's content, supported by relevant communication theories and expert discussions, reveal the strategic use of social media, particularly TikTok, as a powerful tool for image restoration, reputation enhancement, and increasing political electability. The findings show that short, viral videos on TikTok can significantly reshape public perceptions, even of controversial leaders, by packaging light, entertaining content infused with subtle political messaging. This study contributes to the growing discourse on the intersection of digital media and political communication by providing new insights into how emotional appeals, symbolism, and algorithm-driven exposure on social platforms can influence political narratives. It highlights the transformation of TikTok from a mere entertainment medium into a political stage, especially in the context of the 2024 Indonesian presidential election. The research underscores the importance of critical media literacy among voters, especially Gen Z, who dominate social media usage. In conclusion, political communication in the digital era is no longer confined to traditional media but is increasingly shaped by the virality, visual language, and emotional engagement that platforms like TikTok afford.